College education management system (CEMS) - Muroki, Solomon (Meru: Solomon Muroki Mutuma, 2013)
Globalization and deregulation of economy worldwide has made the service industry highly competitive. Now transaction based approach has evolved further in terms of relationship and solution mindset. Service industry has matured and businesses need to upgrade their processes to remain competitive. Education sector is no longer an exception to it. School management is a crucial area from service delivery perspective and people have started realizing the importance of process automation in colleges. College management software is an IT application that is used to empower schools in managing their activities. College Education Management software is a complete suite of applications that permits you to automate all aspects of school or college management, including student information system, student- grading software. It permits you to capture,manipulate and present student data in a meaningful manner, generate reports and statistics dynamically. College education software is an attempt to incorporate IT in operations and management of college that results in greater efficiency and effectiveness. College education management system is software that is preapred to maintai n day to day operations of a college. This software will help the institution maintain students and employee records.College Education Management System is software has the perspective of attaining attraction of those colleges which don't have one good performing software for keeping their information secure and make their management easier. College education management system provides one attractive environment where you can manipulate data and information about students and staff easily.So we can say the core purpose of designing "College education management systems" is to manage the task related to the college students/ employee and to reduce time to searching of appropriate candidates in college view.
This project is submitted in partial fulfillment of requirement for Meru University of Science and Technology award of Bachelor of Science in Information Techonolgy